1969
DOI: 10.1063/1.1657359
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydrodynamic Ion Source

Abstract: An electrohydrodynamic (EHD) technique is used to generate ions from liquid metals. Liquid metal is fed to the tip of a capillary needle emitter with a voltage difference applied between the emitter and an extractor electrode to produce an intense electric field at the liquid surface. Electrostatic forces overcome surface tension forces to produce ions by field emission. When using liquid cesium, time-of-flight mass analysis showed the ion current to be primarily Cs+ with a small percentage of Cs2+ and Cs3+. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…by the fact that even stable liquid metal sprays can be established under vacuum conditions for the direct production of (d) Effect of the Liquid Electric Conductivity and of metal ions (25,26 Since it has been shown that the most important liquid V 01 cm 01 to 10 07 V 01 cm 01 , with the resulting sprays prophysical property in controlling both the stability of the elecducing droplets in the submicron size range. trospray (4,14) and the size of the droplet (13,15) is the In the present study the effect of the liquid electric conducliquid electric conductivity, our investigation mainly focused tivity was studied by doping heptane with different concenon this parameter among all liquid physical properties.…”
Section: ) (C) Effects Of the Capillary Diameter And Of Thementioning
confidence: 99%
“…by the fact that even stable liquid metal sprays can be established under vacuum conditions for the direct production of (d) Effect of the Liquid Electric Conductivity and of metal ions (25,26 Since it has been shown that the most important liquid V 01 cm 01 to 10 07 V 01 cm 01 , with the resulting sprays prophysical property in controlling both the stability of the elecducing droplets in the submicron size range. trospray (4,14) and the size of the droplet (13,15) is the In the present study the effect of the liquid electric conducliquid electric conductivity, our investigation mainly focused tivity was studied by doping heptane with different concenon this parameter among all liquid physical properties.…”
Section: ) (C) Effects Of the Capillary Diameter And Of Thementioning
confidence: 99%
“…The basic principle (see, e.g. Mahoney et al, 1969) has undergone a major redesign to qualify the sources for space use (see Fehringer et al, 1997). For this instrument, indium (stable isotopes with 115 amu and 113 amu to 95.7% and 4.3%, respectively) has been chosen as the ion-source charge material due to its low vapour pressure, which prevents the contamination of the source insulators and ambient spacecraft surfaces.…”
Section: The Ion Emittersmentioning
confidence: 99%
“…This development was also based on experiments on the emission of caesium ions from capillary tubes. 8 At the European Space Research and Technology Centre (ESTEC), a field emission or FEEP system based on the liquid metal ion source principle with caesium as the propellant has been developed progressively and evolved from a singlepin emitter through linear arrays of stacked needles to the presently favoured slit emitter module. 3 Homogeneous high current ion emission from a micron-sized slit has been demonstrated successfully, 9,10 allowing the occurrence of a linear series of equally spaced emitting sites with a distance of <10 5 m and a linear current density of >5 ð 10 1 A m 1 .…”
Section: Historical Backgroundmentioning
confidence: 99%